Gutierre de Cetina, Rimas. Ed. de Jesús Ponce Cárdenas. Cátedra, Madrid, 2014; 1238 pp. - Barragán Aroche, Raquel (Nueva Revista de Filología Hispánica (NRFH), 2015)
Se reseña el libro: Rimas. Ed. de Jesús Ponce Cárdenas.